1997
DOI: 10.1086/297794
|View full text |Cite
|
Sign up to set email alerts
|

Pluralistic Ignorance Across Issues and Over Time: Information Cues and Biases

Abstract: Pluralistic ignorance is a well-documented phenomenon in public opinion research. We adopt the social perspective on pluralistic ignorance and focus on the information environment for an explanation of it. Regarding pluralistic ignorance as a problem of information, we consider its implications in terms of cross-sectional variation as well as over time. The empirical analysis combines a comparative study of issues and analysis over time of gender issues and the question of returning territories for peace in Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 24 publications
2
63
0
Order By: Relevance
“…However, distortions of this general tendency can arise when a minority opinion is given disproportionate prominence in public debate and by the media, in which case the actual majority of people may think that their opinion is in the minority. This mistaken perception is known as pluralistic ignorance (Shamir and Shamir, 1997;Todorov and Mandisodza, 2004). A recent example involves the American public's perceptions of their own opinions regarding U.S. foreign policy in the aftermath of the terrorist attacks of 9/11: although only a minority of people (around 25%) thought that the proper policy response was for the U.S. to work unilaterally to combat terrorism, rather than in concert with other nations, the people who held this minority view thought that around half the public endorsed their unilateral approach (Todorov and Mandisodza, 2004).…”
Section: Pluralistic Ignorance and False Consensus Effectmentioning
confidence: 99%
“…However, distortions of this general tendency can arise when a minority opinion is given disproportionate prominence in public debate and by the media, in which case the actual majority of people may think that their opinion is in the minority. This mistaken perception is known as pluralistic ignorance (Shamir and Shamir, 1997;Todorov and Mandisodza, 2004). A recent example involves the American public's perceptions of their own opinions regarding U.S. foreign policy in the aftermath of the terrorist attacks of 9/11: although only a minority of people (around 25%) thought that the proper policy response was for the U.S. to work unilaterally to combat terrorism, rather than in concert with other nations, the people who held this minority view thought that around half the public endorsed their unilateral approach (Todorov and Mandisodza, 2004).…”
Section: Pluralistic Ignorance and False Consensus Effectmentioning
confidence: 99%
“…Although pluralistic ignorance is a well-documented phenomenon across various issues at both individual and societal levels (Shamir and Shamir 1997), the attempts to find out the sources of pluralistic ignorance are relatively scarce. In one study, Miller and McFarland (1987) showed that the fear of embarrassment and social identity had causal influences on pluralistic ignorance.…”
Section: Third-person Perception As a Predictor Of Pluralistic Ignorancementioning
confidence: 99%
“…Researchers of pluralistic ignorance have long believed that communication, either interpersonal or mass-mediated, is a critical factor in determining the accuracy of perceived climate of opinions (Taylor 1982). Noelle-Neumann (1974) emphasized the role of mass media in the formation of pluralistic ignorance and a macro-level survey study (Shamir and Shamir 1997) demonstrated that the amount of media coverage was a necessary, if not sufficient, condition to reduce pluralistic ignorance. The investigation of the media as the cause of pluralistic ignorance is rare at the individual level, too.…”
Section: Third-person Perception As a Predictor Of Pluralistic Ignorancementioning
confidence: 99%
“…Therefore, inaccurate judgment of the social norm caused a reversal of the illusion of universality, leading the group to a situation of pluralistic ignorance. Pluralistic ignorance, in the vision of Shamir and Shamir (1997), is a set of cognitive beliefs, shared by two or more people about ideas, feelings or actions of others. Saito and Obushi (2014) differentiate between perceptual and inferential pluralistic ignorance.…”
Section: Pluralistic Ignorance: Concept and Classificationmentioning
confidence: 99%